2019
DOI: 10.1111/jfpp.13955
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microbiological and physico‐chemical parameters of retail ready‐to‐eat mono‐varietal salads

Abstract: An integrated microbiological and physico‐chemical approach was applied to evaluate the decay of mono‐varietal ready‐to‐eat escarole (Cichorium endivia var. latifolium) and red chicory (Cichorium intybus L. var. foliosum Hegi) during refrigeration. Total mesophilic microorganisms, including pseudomonads, and total psychrotrophic microorganisms were detected at high numbers in all samples just after packaging and at the expiry date. The dominant microbial populations analyzed by classical culture‐dependent meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…Minimally processed borage leaves stored at 2 °C had an OQ score higher than four after 14 d and were still marketable after 21 d of cold storage. Minimally processed borage leaves exhibited a shelf life longer than the expiration date usually adopted for fresh-cut vegetables (7-10 d), especially when stored continuously at a low temperature, as was also found for other minimally processed leafy vegetables packed in plastic bags [40,43,[47][48].…”
Section: Resultssupporting
confidence: 55%
“…Minimally processed borage leaves stored at 2 °C had an OQ score higher than four after 14 d and were still marketable after 21 d of cold storage. Minimally processed borage leaves exhibited a shelf life longer than the expiration date usually adopted for fresh-cut vegetables (7-10 d), especially when stored continuously at a low temperature, as was also found for other minimally processed leafy vegetables packed in plastic bags [40,43,[47][48].…”
Section: Resultssupporting
confidence: 55%
“…Lers et al [74] found that preharvest GA 3 treatments were effective in reducing the respiration rate of parsley leaves stored for 8 d at 25 • C, while in our experiment we did not find a modification of metabolites (soluble sugars or total acidity) that could have confirmed the effect of GA 3 on respiration rate. This was probably due to the low temperature and to the atmosphere inside the sealed bags that was effective in slowing the respiration process [65,75].…”
Section: Discussionmentioning
confidence: 99%
“…• Brix at day 0 and remained almost constant until the end of cold storage (5.5 • Brix on average at day 14) ( Table 3). As reported by others authors for various leafy vegetables [26,[35][36][37][38][39], minimally-processed vegetables packed in sealed plastic bags characterized by low permeability to water vapor do not suffer dehydration due to the very high relative humidity inside the sealed packages (near to 100%). Moreover, fresh-cut leafy vegetables cold stored in sealed plastic films usually have a low respiration rate [36][37][38], as confirmed by the small variation of TSS recorded for the borage samples irrespective of accession and plant density ( Table 3).…”
Section: Source Of Variancementioning
confidence: 80%
“…Total soluble solids were on average 5.9 °Brix at day 0 and remained almost constant until the end of cold storage (5.5 °Brix on average at day 14) ( Table 3). As reported by others authors for various leafy vegetables [26,[35][36][37][38][39], minimally-processed vegetables packed in sealed plastic bags characterized by low permeability to water vapor do not suffer dehydration due to the very high Consumer's perception of vegetable quality is mainly influenced by their color and appearance; thus, color modifications and overall appearance are the primary parameters for the quality evaluation of vegetables, especially those minimally-processed [44,48]. These modifications may occur due to both pre-harvest [48][49][50][51][52] or post-harvest [17,19,[35][36][37]53,54] factors.…”
Section: Source Of Variancementioning
confidence: 86%